Pengaruh Kecepatan Dan Arah Aliran Udara Terhadap Kondisi Udara Dalam Ruangan Pada Sistem Ventilasi Alamiah - Utami Dewi, Francisca Gayuh (Rekayasa Mesin, 2012)
Natural ventilation should be regarded to maintain room air condition with respect to health and satisfaction of people in the room. Outside air flow into the room, so air exchanges occur. Principally natural air exchange is caused by the different between pressure inside and outside the room, as a result of thermal and velocity factors.The study is conducted experimentally. The influence of air velocity and direction of air to the room air condition are studied by observation on a model placed in a wind tunnel. The model was scaled 1 : 10 to the prototype. The study was conducted using velocity of flow air variation (1 m/s, 2 m/s, 3 m/s, 4 m/s, 5 m/s, 6 m/s and 7 m/s) and the angle direction of flow (0o, 10o and 15o). The result of the study shows that velocity and direction of air flow determine air condition in the room indicated by air circulation, heat energy exhausted by the circulated air, and ventilation coefficient. The higher heat absorption was occurred for velocity of 7 m/s and direction of flow 15o, 10o and 0o subsequently.Keywords: natural ventilation, air flow velocity, direction of flow.